Henle fiber layer thickening and deficits in objective retinal function in participants with a history of multiple traumatic brain injuries - Stern-Green, Elizabeth A.; Klimo, Kelly R.; Day, Elizabeth; Shelton, Erica R.; Robich, Matthew L.; Jordan, Lisa A.; Racine, Julie; VanNasdale, Dean A.; McDaniel, Catherine E.; Yuhas, Phillip T. (Frontiers in Neurology, 2024)
Introduction This study tested whether multiple traumatic brain injuries (TBIs) alter the structure of the Henle fiber layer (HFL) and degrade cell-specific function in the retinas of human participants. Methods A cohort of case participants with multiple TBIs and a cohort of pair-matched control participants were prospectively recruited. Directional optical coherence tomography and scanning laser polarimetry measured HFL thickness and phase retardation, respectively. Full-field flash electroretinography (fERG) assessed retinal function under light-adapted (LA) 3.0, LA 30 Hz, dark-adapted (DA) 0.01, DA 3.0, and DA 10 conditions. Retinal imaging and fERG outcomes were averaged between both eyes, and paired t-tests or Wilcoxon signed-rank tests analyzed inter-cohort differences. Results Global HFL thickness was significantly (p = 0.02) greater in cases (8.4 ± 0.9 pixels) than in controls (7.7 ± 1.1 pixels). There was no statistically significant difference (p = 0.91) between the cohorts for global HFL phase retardation. For fERG, LA 3.0 a-wave amplitude was significantly reduced (p = 0.02) in cases (23.5 ± 4.2 μV) compared to controls (29.0 ± 8.0 μV). There were no other statistically significant fERG outcomes between the cohorts. Discussion In summary, the HFL thickens after multiple TBIs, but phase retardation remains unaltered in the macula. Multiple TBIs may also impair retinal function, indicated by a reduction in a-wave amplitude. These results support the potential of the retina as a site to detect TBI-associated pathology.